National Socio-Psychological Methods of Educating Positive Qualities in the Behavior of Young People - Jabborov, Kh. Kh. (International Journal on Human-Computing Studies, 2023)
In this article, one can see the originality of worldview and socio-psychological factors in the education of positive qualities among young people, as well as pedagogical methods and socio-psychological approaches to education, prepared on the basis of local history research.